Celebrating queer lesbian desires with Dorothy Allison: From moral monstrosity to the beautiful materiality of the body - Mélanie Grué (2015)
Using social and queer theory on domination, sexuality and gender, this contribution explores how the queer American author Dorothy Allison celebrates the vilified transgressive lesbian body. As, in the 1970s, the mainstream american feminist movement crystallized around the definition of an acceptable sexuality in the name of femininity, female sexual practices were standardized according to strict identity frames, carnal desire was denied, and transgressive lesbians who play with gender roles were defined as abject. In response to this extreme taming of the body, Allison interrogates the notions of masculinity and femininity, domination and submission in her exploration of sexual pleasure and traumatized sexuality. She celebrates the aggressiveness and masculinity of queer lesbianism, promotes the fluidity of gender roles, and asserts the primacy of the flesh,sensuality, and materiality in sexuality.
Keywords: approches et analyses; arts; corps; corps lesbien; discipline; identités LGBTQIA2+; littérature; personnes lesbiennes; queer; ressource en ligne; sexualité; thématiques; études littéraires

“Great writing always sings”: Dorothy Allison Speaks - Grué, Mélanie; Allison, Dorothy (The Southern Quarterly, 2016)
Brought up in a Southern poor white family and the victim of her stepfather's abuse from a very early age, Allison turned to writing to address difficult issues which few writers dare to deal with: child abuse, class-based discrimination, transgressive lesbianism, and overall violence. [...]I started burning them, or destroying them. Because they were just too dangerous to be in the world. Some of it is not so bad: bluegrass and rhythm 'n' blues, some of the gospel music I love, it stays with me.
Keywords: amériques; approches et analyses; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; écriture des femmes*; états-unis